Assessment for Learning: The Role of Feedback in Student Academic Development - Yusuf Al-Kareema; Ahmad Al-Hakimi (Innovative Journal of Educational Research and Insights, 2026)
This study explores the role of feedback in Assessment for Learning and its impact on student academic development. Using a qualitative descriptive approach, data were collected through interviews, classroom observations, and document analysis involving teachers and students. The findings indicate that effective feedback significantly enhances students’ understanding of learning objectives, improves the quality of their work, and fosters greater engagement in the learning process. Feedback also contributes to the development of metacognitive skills, enabling students to reflect on their performance and take responsibility for their own learning. Furthermore, the study reveals that feedback supports student motivation by creating a positive and encouraging learning environment. However, challenges such as time constraints, large class sizes, and students’ limited ability to utilize feedback effectively were identified. The study concludes that well-designed feedback practices, supported by appropriate instructional strategies and technology, are essential for maximizing the effectiveness of Assessment for Learning.